Phylogenetic revision of Camarosporium (Pleosporineae, Dothideomycetes) and allied genera - Wanasinghe, D.N. (Stud Mycol, 2017)
A concatenated dataset of LSU, SSU, ITS and tef1 DNA sequence data was analysed to investigate the taxonomic position and phylogenetic relationships of the genus Camarosporium in Pleosporineae (Dothideomycetes). Newly generated sequences from camarosporium-like taxa collected from Europe (Italy) and Russia form a well-supported monophyletic clade within Pleosporineae. A new genus Camarosporidiella and a new family Camarosporidiellaceae are established to accommodate these taxa. Four new species, Neocamarosporium korfii, N. lamiacearum, N. salicorniicola and N. salsolae, constitute a strongly supported clade with several known taxa for which the new family, Neocamarosporiaceae, is introduced. The genus Staurosphaeria based on S. lycii is resurrected and epitypified, and shown to accommodate the recently introduced genus Hazslinszkyomyces in Coniothyriaceae with significant statistical support. Camarosporium quaternatum, the type species of Camarosporium and Camarosporomyces flavigena cluster together in a monophyletic clade with significant statistical support and sister to the Leptosphaeriaceae. To better resolve interfamilial/intergeneric level relationships and improve taxonomic understanding within Pleosporineae, we validate Camarosporiaceae to accommodate Camarosporium and Camarosporomyces. The latter taxa along with other species are described in this study.